Analysis of Human Capital Accounting and Intellectual Capital on Financial Performance in Technology Companies in Indonesia - Suparjiman Suparjiman; Helda Yusita (Westscience Press, 2026)
This study examines the influence of human resources and intellectual capital accounting on the financial performance of technology companies in Indonesia. The increasing dependence of technology companies on employee competence, organizational knowledge, innovation, information systems, and stakeholder relationships highlights the importance of intangible resources in supporting sustainable business performance. This study employed a quantitative research design using primary data collected through a structured questionnaire measured on a five-point Likert scale. A total of 175 respondents from technology companies in Indonesia participated in the study. The data were analyzed using SPSS version 25 through descriptive statistics, validity and reliability tests, classical assumption tests, multiple linear regression analysis, partial t-tests, simultaneous F-tests, and the coefficient of determination. The results showed that human resources had a positive and significant effect on financial performance. Intellectual capital accounting also had a positive and significant effect on financial performance. Simultaneously, human resources and intellectual capital accounting significantly influenced financial performance, as indicated by an F-value of 72.184 and a significance value below 0.001. The R-square value of 0.457 indicates that the two independent variables explain 45.7% of the variation in financial performance. These findings demonstrate that employee capabilities and systematic intellectual capital accounting practices are essential for improving profitability, operational efficiency, revenue growth, and financial sustainability in Indonesian technology companies.